2012
DOI: 10.1111/bjso.12001
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name? Our false uniqueness!

Abstract: The current study investigated our perception of first names. In Study 1, participants estimated their own first name to be less frequent compared with estimates from yoked controls. The first name uniqueness effect was seen for both rare and common names, and male and female names. The uniqueness bias was not due to differential encoding of variegated and shortened names, such as different versions of the name Caitlyn. Study 2 established that rarer names are preferred, and, that when we contemplate a name ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Furthermore, our results suggest that the stereotype of unique names may be embodied in real name changes (Studies 5a–5b; cf. Kulig, 2013; Zwebner et al., 2017) and may have beneficial real‐world consequences for product evaluation (Study 6). In summary, our findings suggest that unique names can be a double‐edged sword, with relatively positive perceptions and implications for creative domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results suggest that the stereotype of unique names may be embodied in real name changes (Studies 5a–5b; cf. Kulig, 2013; Zwebner et al., 2017) and may have beneficial real‐world consequences for product evaluation (Study 6). In summary, our findings suggest that unique names can be a double‐edged sword, with relatively positive perceptions and implications for creative domains.…”
Section: Discussionmentioning
confidence: 99%
“…A person's name is often viewed as a symbol of their identity (Allport, 1937; Kulig, 2013). A unique name may imply an unconventional family or cultural background (Fryer & Levitt, 2004; Lieberson & Bell, 1992) and may pose challenges to pronunciation and spelling (Laham et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Young people in their twenties tend to recognize that they are better than average and have a uniqueness. A previous study in social psychology showed that college students believed their names to be unique than those really were ( Kulig, 2013 ). In other words, young people pursue uniqueness even in the characteristics given by others, such as names.…”
Section: Discussionmentioning
confidence: 99%
“…Isso confirma a direção hipotetizada por Suls e Wan (1987) para as situações em que o respondente poderia ser mais benevolente, ou especial, do que amigos ou desconhecidos. Embora alguns estudos recentes tenham retomado o interesse pelo viés de falsa unicidade (p.ex., Kulig, 2013), o fenômeno ainda é pouco investigado e merece uma agenda de pesquisa que possa ser articulada com processos de gerenciamento de impressão, como no caso das desculpas. Apesar dos resultados apresentados neste estudo, é preciso reconhecer alguns elementos que poderiam aprimorar a compreensão do fenômeno de aceitabilidade de desculpas.…”
Section: Discussionunclassified